1986
DOI: 10.1002/bit.260281105
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the liquid flow in up‐flow anaerobic sludge blanket reactors

Abstract: By means of stimulus-response experiments an Li(+) tracer, models for the fluid flow in a 30-m(3) UASB reactor, used for the anaerobic treatment of wastewater, were tested. From the model with the best fit it could be derived that both the sludge bed and the sludge blanket can be described as perfectly mixed tank reactors with short-circuiting flows; the settler volume acts like a plug-flow region.Apart from the volumes of the different flow regions, two parameters are necessary and sufficient to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 4 publications
0
31
0
3
Order By: Relevance
“…1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,17,18,19,20,21,22,23,24,25,26,27,28,29), based on the combination of sludge dynamics and bacterial metabolism. To our knowledge, this is the first successful attempt in the creation of models of a new generation that are able to simulate complex space heterogeneous dynamics, not only of solutes but also of the granular sludge (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,17,18,19,20,21,22,23,24,25,26,27,28,29), based on the combination of sludge dynamics and bacterial metabolism. To our knowledge, this is the first successful attempt in the creation of models of a new generation that are able to simulate complex space heterogeneous dynamics, not only of solutes but also of the granular sludge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…immanent formation and development of sludge bed and blanket zones, sludge wash-out) inside UASB reactors. The second principal difference of the presented model with previously proposed models of UASB reactors [3,36] is that it provides a universal description of both hydrodynamics and solids dynamics by continuous equations throughout the reactor volume. The third prominent feature of the dispersed plug flow model is that it relies solely on internal mechanisms of the bioprocesses to predict sludge washout from the reactor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, the better retention might be associated to the absence of biogas production and thus turbulence. Therefore, in the absence of turbulence, the wastewater flow is more homogeneous [65][66][67][68], and helminth eggs settling follow a discrete settling pattern. Another remarkable observation is that even at the lowest upflow velocity (0.09 m·h ) helminth eggs do not settle completely nor are retained completely by the sludge bed.…”
Section: Resultsmentioning
confidence: 99%
“…In treating cane sugar wastewater, it was observed that at low organic loading rates, adequate mixing of an U4SB reactor contents did not take place (Manjunath et ai.. 1989). Bolle et al (1986) developed a model in which both sludge bed and sludge blanket can be described as completeIy mixed flow reactors with short-circuiting flow paths, while the settler volume was best described as a plug flow reactor. Short-circuiting flow through the sludge bed was a function of the bed height.…”
Section: Introductionmentioning
confidence: 99%